Investigation into the possibility of applying lubrication theory to the selection of optimum clearance fits for plain hydrodynamically lubricated bearings - Loxham, J. (College of Aeronautics, 1964)
BS1916 limits and fits for engineering is based on ISA bulletin 25 which was first issued in 1921 and designed for use with the metric system. It provides a wide range of tolerances for holes and shafts from which it is possible by suitable selection to satisfy a wide range of engineering requirements. The basic principle underlying the system is the allocation of letters to signify the magnitude of the displacement of that part of the tolerance zone which is nearest to the basic size and a number to indicate the magnitude of the tolerance. Capital letters are used for holes, small letters for shafts. The numbers referred to as fundamental tolerances are common to holes and shafts. In applying the system to inch sizes care was taken to ensure that fit combinations (H6/k4) would provide the same type of fit in the inch system as was established in the metric system throughout the whole of the Size range. It was also recommended that a unilateral hole basis be adopted in which the hole is the standard member and the tolerance specified as a value from nominal to plus an amount determined.by the number signifying the magnitude of the tolerance. Different types of fit are obtained by selecting from the standard shafts available the one whose fundamental deviation from basic size is considered to be the most suitable and :allocating to it a suitable standard tolerance When ISA bulletin 25 was issued great care was taken in selecting the disposition of the sizes allocated to standard shafts so that when one standard shaft was used with one standard hole it would provide a fit which -mould be functionally similar throughout the complete range of sizes. The decision of I.S.O. and B.S.I. to extend the size range from 20 inches to 200 inches caused reasonable doubts to exist about the reliability of this simple rule that one fit combination would be functionally similar throughout the whole of the extended size range. As this problem was examined in more detail cases were found where the above rule was not satisfactory over the extended or the smaller size range covered by the original standard (0.040” to 20”). In considering the possibility of applying theoretical analysis to this problem it was clear that the most difficult section was that concerned with the selection of clearance fits for hydrodynamically lubricated plain 'beatings. The present paper is a preliminary survey into this problem and the detailed analysis is restricted to the application of lubrication theory to the selection of what appear to be optimum clearance fits for hydrodynamically lubricated bearings and the means that may be used for comparing these results with the recommendations of I.S.A. bulletin 25 and BS1916. Figure 1 is a simplified representation of a plain bearing operating under conditions of hydrodynamic lubrication.